Weak gravitational lensing around dyonic ModMax black hole in plasma - Turakhonov, Ziyodulla; Atamurotov, Farruh; Övgün, Ali; Abdujabbarov, Ahmadjon; Urinov, Sunnatillo (Iop Publishing Ltd, 2024)
In this study, we examine the effects of weak gravitational lensing and determine the shadow radius around black holes within the Dyonic ModMax (DM) spacetime, also accounting for models with nonuniform plasma distributions. By analyzing various gravitational lens models, we compare corrections to vacuum lensing due to gravitational effects within plasma and plasma inhomogeneity, finding that these effects could be observed in hot gas within galaxy clusters. Starting with the orbits of photons around a black hole in DM, we investigate the shadow and weak gravitational lensing phenomena. Utilizing observational data from the Event Horizon Telescope for M87* and SgrA*, we constrain parameters within DM gravity. To connect our findings to observations, we examine the magnification and positioning of lensed images, along with the weak deflection angle and magnification for sources near different galaxies.
Keywords: black hole; gravitational lensing; modified gravity; plasma medium